The Impact of Positive Emotional Appeals on the Green Purchase Behavior - Wang, Jianming; Yang, Xincheng; He, Zhengxia; Wang, Jianguo; Bao, Jing; Gao, Jian (Frontiers in Psychology, 2022)
The practice of green consumption has become a common initiative of the international community. Existing studies have shown that emotional factors have an important impact on consumer behavior, but few scholars in the field of green consumption behavior have explored the relationship between positive emotions and green purchase behavior in specific dimensions. This study creatively put forward two dimensions and four kinds of positive emotional appeals which include the cherishing appeal, the yearning appeal, the proud appeal and the admiring appeal. Through the conceptual model analysis based on the data, the effects of different four positive emotional appeals on consumers’ perceived green value, perceived green responsibility, green purchase behaviors were confirmed. The results indicated that the four kinds of positive emotional appeals, perceived green value, perceived green responsibility, green purchase behavior were positively correlated. Perceived green responsibility and perceived green value has significant mediating effect on the relationship between positive emotional appeals and green purchase behaviors. Middle doctrine significantly moderates the relationship between positive emotional appeals(Cherishing VS. Yearning) and perceived green value.